Ideologi Kapitalisme dalam Iklan Rokok Djarum 76 Edisi Wani Piro: Kajian Analisis Wacana Kritis - Reci Apreno; Noermanzah Noermanzah (Silampari Bisa: Jurnal Penelitian Pendidikan Bahasa Indonesia, Daerah, dan Asing, 2020)
The development of advertising is currently growing rapidly in line with technological developments that are increasingly unstoppable. Indeed, advertising is a medium used by a company or business entity to promote goods or services that have a persuasive language and have an ideology of capitalism. However, currently there are several advertisements that do not use persuading language, but want to incorporate elements of capitalism, such as the Djarum 76 ad that will be discussed in this study. This research will describe the ideology of capitalism in the Djarum 76 cigarette advertisement edition of Wani Piro. The research method used is the Norman Fairclough model of critical discourse analysis. The object or data in this study is the oral discourse contained in the Djarum 76 cigarette advertisement edition of Wani Piro. The technique in collecting data is done by documentation technique sourced from YouTube. In the data analysis activities in accordance with the Norman Fairclough model there are three steps of analysis namely, analysis at the level of the text, discourse practices, and socio-cultural practices. Data validity is done by member checking and expert discourse test. The results of this study indicate that the words used are more unique and funny words, and the Djarum 76 advertisement is packaged with a form of critical discourse as if concerned with the social conditions of the community. However, behind the critical discourse that is used, veiled an ideology that is capitalism in accordance with the purpose of an advertisement that is looking for profit from the product being promoted.